2020
DOI: 10.2217/pgs-2019-0134
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomics at the Center of Precision Medicine: Challenges and Perspective in an Era of Big Data

Abstract: Pharmacogenomics (PGx) is one of the core elements of personalized medicine. PGx information reduces the likelihood of adverse drug reactions and optimizes therapeutic efficacy. St Catherine Specialty Hospital in Zagreb/Zabok, Croatia has implemented a personalized patient approach using the RightMed® Comprehensive PGx panel of 25 pharmacogenes plus Facor V Leiden, Factor II and MTHFR genes, which is interpreted by a special counseling team to offer the best quality of care. With the advent of significant tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 90 publications
0
21
0
1
Order By: Relevance
“…Incorporating pharmacogenomics into practice enables prescribers to follow a personalized medicine approach which can ultimately optimize therapy, reduce adverse effects and drug-drug interactions[ 56 ]. Patients living with HIV and/or TB are one of many patient groups who can benefit from pharmacogenomics implementation.…”
Section: Introductionmentioning
confidence: 99%
“…Incorporating pharmacogenomics into practice enables prescribers to follow a personalized medicine approach which can ultimately optimize therapy, reduce adverse effects and drug-drug interactions[ 56 ]. Patients living with HIV and/or TB are one of many patient groups who can benefit from pharmacogenomics implementation.…”
Section: Introductionmentioning
confidence: 99%
“…Precision medicine relies on how an individual’s unique molecular profile influences the individual’s susceptibility to disease and response to medical treatment [ 13 ]. Over the past few years, there has been a paradigm shift from a ‘one drug fits all’ traditional approach to a personalized patient orientated approach [ 14 ]. It has been reported that about 95% of an individuals’ drug response is attributed to genetic elements [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although drugs are generally effective and used with low risks of adverse events, response to drugs varies among individuals. Knowledge of variants in genes associated with drug response (pharmacogenes) is vital for optimizing an individual's therapeutic outcome [4]. Pharmacogenes include genes governing pharmacokinetics (PK), i.e., Cytochrome P450 genes, receptor/transporter genes (drug targets) governing pharmacodynamics (PD), and genes with functions related to immune-mediated adverse drug reactions (IM-ADR), i.e., human leukocyte antigen (HLA) genes.…”
Section: Introductionmentioning
confidence: 99%